AB0312 Changes in the levels of interferon-gamma in quantiferon tb gold test during the biological treatment. (23rd January 2014) - Zanova, E.; Kozakova, D.; Rybar, I.; Solovic, I.; Rovenský, J.
Abstract : Background: IGRA tests decrease the risk of false negative results, present the development of active disease, eliminate the mistakes in the interpretation of skin tuberkulin test, accelerate establishment of diagnosis and initiation of soon adequate therapy. QFT-G IT result is obtained by calculation of the interferon-gamma level in Mitogen, TB antigen and Nil blood tube using QFT analysis software. Objectives: To determine the level of INF-γ in conversions of originally QFT- G IT negative results to QFT- G IT positive results in patients treated in 2012. To determine differences in INF-γ levels in patients with conversion of QFT using the following critheria TB Antigen minus Nil, Mitogen minus Nil (IU/mL). Methods: The latent Mycobacterium tuberculosis infection in blood was determined by QFT- G IT (IGRA - ELISA test with special blood collection tubes coated with TB antigens, cellestis). We observed the group of patients who fulfilling the diagnostic critheria of rheumatoid arthritis, psoriatic arthritis and ankylosing spondylitis and the critheria for the biologic treatment Results: We examined 930 patients with biological treatment. Negative results were found in 870 patients (93, 55%), positive in 60 patients (6, 45%). From 60 QFT- G IT positive were 20 patients first detected (new patients), 25 repeatedly detected as positive (from 2009-2012) and 15 patients with conversion of negative before to QFT-G IT positive results during the biologic treatment in 2012 - 5 of them were treated by tocilizumab, 4 by golimumab, 2 by adalimumab, 3 by etanercept and 1 study patient. In this group of patients (15/60) the average level of INF-γ in the tube of TB Antigen minus Nil was 0, 082 IU/ml and in the tube of Mitogen minus Nil 11, 154 IU/ml before QFT conversion. We observed an increase of INF-γ levels after QFT conversion during the biological treatment: the value of INF-γ in the tube of TB antigen minus Nil was 3, 708 IU/ml and in the tube of Mitogen minus Nil 16, 23 IU/ml. A statistically significant 72 fold increase of INF-γ level was found in the group of patients with QFT conversion (TB Antigen minus Nil) against 1, 45 fold increase of INF-γ level in Mitogen – Nil. The comparison with the group of 25 QFT positive patients before and during the biological treatment showed, that levels of INF-γ in connection with the biological treatment remain not statisticly changed - TB antigen minus Nil before biological treatment was 4, 58 IU/ml to level 3, 19 IU/ml during the treatment, Mitogen minus Nil before 20, 84 to level 14, 60 IU/ml during the treatment. Conclusions: A statistically significant increase of INF-γ levels was observed in the group of patients with QFT corversion (TB Antigen minus Nil) during the biological treatment. The differences between INF-γ levels in a group of QFT positive patients before and during the biological treatment was not found. The increase of QFT conversion was observed at IL-6 blocker treatment, and then at conventional anti-TNF treatment. This finding raises a question of INF-γ increase level by actual biological treatment. On the other hand, the patients with positive QFT showed not statisticly reduced levels of INF-γ before and during the biological treatment. References: Kharbanda, P, Dagaonkar, R., Balakrishnan, C., Udwadia, Z.F. Tumor necrosis factor – α blocker induced tuberculosis. J. Rheumatol 2010, 37: 7-11 Disclosure of Interest: None Declared